A Learner Centered Approach: ESP Need Analysis in Pandemic Learning Activities for Non Formal Students in High School Equivalency, Coastal Area of Bone Bolango - Haris Danial; Nonny Basalama; Riman Kasim (Ideas Publishing, 2022)
Learning activities in the world of equality education need attention from every tutor who teaches in the classroom. Especially in learning English, there are still many students who are constrained in understanding English well. This is because the backgrounds of students are varied, resulting in their lack of motivation in learning. The method used in this research is the method of developing teaching materials in equivalence education, especially the Package C equivalence program in the coastal area. This research leads to R&D development research which emphasizes that research and development is a research method used to produce certain products and test the effectiveness of products. The results of this study found that the application of storytelling activities using animation that was done well and repeatedly would be able to improve English language skills. It is evident from the results of the research conducted, which then increased the results of the independent sample t-test calculation, it is known that the average increase in the experimental group I was 35, group II was 43.85, and group III was 30.45. Thus, it is known that the increase in the score of learning outcomes in the Analysis of English Learning Needs for School Dropouts in the Experimental Coastal Equality School, the most prominent is in group II of 43.85 Kegiatan pembelajaran di dunia pendidikan kesetaraan perlu mendapat perhatian dari setiap tutor yang turut mengajar di dalam kelas. Khususnya dalam pembelajaran bahasa Inggris, masih banyak peserta didik terkendala dalam memahami bahasa inggris dengan baik. Hal ini dikarenakan latar belakang peserta didik yang bervariatif sehingga mengakibatkan kurangnya motivasi mereka dalam belajar. Metode yang digunakan dalam penelitian ini adalah metode pengembangan bahan ajar di pendidikan kesetaraan, khususnya program kesetaraan Paket C yang berada wilayah pesisir. Penelitian ini mengarah pada penelitian pengembangan R&D yang menekankan bahwa penelitian dan pengembangan merupakan metode penelitian yang digunakan untuk menghasilkan produk tertentu dan menguji keefektifan produk. Hasil penelitian ini menemukan bahwa Penerapan kegiatan bercerita menggunakan animasi yang dilakukan dengan baik dan berulang-ulang akan dapat meningkatkan kemampuan berbahasa inggris. Terbukti dari hasil penelitian yang dilakukan, kemudian mengalami peningkatan hasil perhitungan independent sampel t-test diketahui rata-rata kenaikan kelompok eksperimen I sebesar 35, kelompok II sebesar 43.85, dan kelompok III sebesar 30.45. Dengan demikian, diketahui kenaikan skor hasil belajar Analisis Kebutuhan Pembelajaran Bahasa Inggris bagi Anak Putus Sekolah di Sekolah Kesetaraan Wilayah Pesisir eksperimen yang paling menonjol terdapat pada kelompok II sebesar 43.85.